2004
DOI: 10.1080/09540120410001683402
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of antiretroviral adherence

Abstract: This study was conducted in order to help determine the key factors that predict adherence to antiretroviral medications. A total of 115 HIV/AIDS patients who were having trouble adhering to their antiretroviral regimens completed face-to-face interviews in which adherence levels, medication side effects, mental health, social support, patient-provider relationship characteristics, substance use and health anxiety were assessed. Three measures of adherence were used: adherence over the past three days, adheren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
87
2
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(99 citation statements)
references
References 51 publications
8
87
2
2
Order By: Relevance
“…Some researchers have suggested that reduced adherence to ART rather than the effects of alcohol per se may account for the disease progression (Conigliaro et al, 2003;Murphy et al, 2004;Samet et al, 2003). Findings from the study reported here support this view and we propose that the link between alcohol consumption and lower adherence may derive from purposive decision making based on beliefs about the appropriateness of drinking and taking ART, not alcohol induced forgetfulness.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Some researchers have suggested that reduced adherence to ART rather than the effects of alcohol per se may account for the disease progression (Conigliaro et al, 2003;Murphy et al, 2004;Samet et al, 2003). Findings from the study reported here support this view and we propose that the link between alcohol consumption and lower adherence may derive from purposive decision making based on beliefs about the appropriateness of drinking and taking ART, not alcohol induced forgetfulness.…”
Section: Discussionsupporting
confidence: 78%
“…Although the studies discussed above suggest that non-adherent behavior derives from alcohol-induced memory lapses (e.g., Murphy et al, 2004) or from alcohol "blurring" the importance of dose timing, another possible explanation is that patient beliefs about the deleterious effects of drinking alcohol and taking ART may contribute to non-adherence. Beliefs about ART have previously been associated with several aspects of adherence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, a patient's relationship with their health care provider plays an important role in adherence (Altice et al 2001;Heisler et al 2002;Murphy et al 2004;Schneider et al 2004). In a longitudinal analysis of adherence to HIV medication, Godin et al (2005) found patient-doctor satisfaction to be a significant predictor of attitude.…”
Section: Theoretical Perspectivementioning
confidence: 99%
“…However, majority of studies have focused only on the administration of prescribed dose, and have classified participants into adherers or nonadherers based on whether they take a certain percentage of prescribed medication during a time period (Catz, Kelly, Bogart, Benotsch, & McAuliffe, 2000;Chesney et al, 2000;Garcia de Olalla et al, 2002;Knobel et al, 2002). Despite the fact that adherence to instructions regarding dietary requirements, amount and schedule of medications, and lifestyle habits may also substantially influence the efficacy of medication regimens (Altice & Friedland, 1998;Murphy, Marelich, Hoffman, & Steers, 2004;Stone et al, 2001), they have not been well incorporated into the measurement of medication adherence. One recent study employed a more extensive measurement by including more aspects of adherence and found this to be valid and reliable (Reynolds et al, 2007).…”
Section: Measuring Nonadherencementioning
confidence: 99%